ANALISIS PERBANDINGAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII MENGGUNAKAN METODE BLENDING LEARNING DENGAN THINK-TALK-WRITE (TTW) PADA MATERI RELASI DAN FUNGSI - Fitri Cantika; Amin Harahap; Nurlina Ariani Harahap (Universitas Bhinneka PGRI, 2025)
This research aims to determine the involvement of each variable analyzed and the influence of learning outcomes, Blended Learning, and the thinking-speaking-writing method on the relationships and functioning of class VIII Private Alwashliya Simpang Marbau students. This research uses quantitative methods. The population consists of 72 students of Private MTS Alwashliya Simpang Marbau. This data was processed using the SPSS 24 application, which included multiple linear regression tests. The study's findings indicate that the partial test or t-test of learning outcome variables positively and real influences related and functional materials. This can be seen from the T number 3.569 2.00 Relevance value 0.003 0 T table 2.00, Relevance value 0.004 0 2.00 T table, Relevance value 0.000 0. F table 2.77 relevance value 0.001 0.05.